2008
DOI: 10.1677/joe-08-0354
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of toll-like receptor 2 expression improves insulin sensitivity and signaling in muscle and white adipose tissue of mice fed a high-fat diet

Abstract: The aims of the present study were to investigate the expression of toll-like receptor 2 (TLR2) in muscle and white adipose tissue (WAT) of diet-induced obesity (DIO) mice, and also the effects of its inhibition, with the use of TLR2 antisense oligonucleotide (ASON), on insulin sensitivity and signaling. The expression of TLR2 was increased in muscle and WAT of DIO mice, compared with those that received standard chow. Inhibition of TLR2 in DIO mice, by TLR2 ASON, improved insulin sensitivity and signaling in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(94 citation statements)
references
References 33 publications
5
86
1
2
Order By: Relevance
“…Reduced adiposity and reduced hepatosteatosis were also consistent with overall improvements in whole body and hepatic insulin sensitivity as determined by the hyperinsulinaemic-euglycaemic clamp. Thus, our data show for the first time that TLR2 regulates hepatic insulin sensitivity during HFD, extending findings that reduced TLR2 expression by antisense oligonucleotides improved insulin signalling in muscle and white adipose tissue of HFD-fed mice [32]. [12].…”
Section: Discussionsupporting
confidence: 83%
“…Reduced adiposity and reduced hepatosteatosis were also consistent with overall improvements in whole body and hepatic insulin sensitivity as determined by the hyperinsulinaemic-euglycaemic clamp. Thus, our data show for the first time that TLR2 regulates hepatic insulin sensitivity during HFD, extending findings that reduced TLR2 expression by antisense oligonucleotides improved insulin signalling in muscle and white adipose tissue of HFD-fed mice [32]. [12].…”
Section: Discussionsupporting
confidence: 83%
“…In addition to host defense against foreign pathogens, recent studies implicate a role of NF-kB (7,8,9,10,11) and TLR pathway (10,12,13,14,15,16,17,18,19,20) in the pathogenesis of obesity-and type 2 diabetesrelated insulin resistance and metabolic disturbances. Moreover, de Mello et al (10,11) demonstrated that in patients with the metabolic syndrome, the changes in insulin resistance were associated with the changes in the expression of genes involved in the NF-kB signaling pathways in peripheral blood mononuclear cells (PBMCs).…”
Section: Introductionmentioning
confidence: 99%
“…A short time ago, several studies highlighted a correlation between type-2 diabetes and obesity which a state of subclinical chronic inflammation in several tissues such as the adipose tissue, liver and hypothalamus (40)(41)(42)(43)(44). Based on this observation, a new hypothesis has been proposed correlating intestinal flora and obesity (Figure 2).…”
Section: Induction Of Subclinical Inflammationmentioning
confidence: 99%